Aprendizagem de relações arbitrárias em crianças com desenvolvimento típico - Kawasaki, Hindira Naomi (Universidade Federal de São Carlos, 2020)
Understanding and using socially agreed codes is important for daily tasks. Considering the peculiarities of the learning process of symbolic behavior, which involves control by arbitrary relations among stimuli, it is extremely important to produce knowledge on the characterization of how this process occurs, as well as procedures that facilitate its teaching. This study aimed to characterize the learning process of arbitrary relations in typically developing children between the ages of 3 and 6 years, and also to assess different procedures for the establishment of arbitrary relations and the equivalence classes formation. Two studies were conducted. In Study 1, the learning of arbitrary relations among stimuli of four sets (six stimuli per set) was investigated, through two fading procedures: static and dynamic (Experiment 1). In addition, learning differences in the trial-and-error procedure were also investigated (Experiment 2). Of the twelve children who participated in Experiment 1, six children learned all the relations, two learned the relations for two stimuli sets, one child learned one stimulus set and three children did not show any learning. An inverse relation was observed between age and the amount of exposure to the procedure until the learning relations, independently of the type of fading. In Experiment 2, seven children (among the oldest in Study 1) were exposed to the trial-and-error procedure, and five of the seven children learned all the relations. In Study 2, also conducted in two experiments, the goal was to investigate the learning of simple discrimination with specific compound consequences of classes and the formation of equivalent stimuli classes in young children. In addition to assessing the possible effects of identity matching training (IDMTS) among the members of the composite consequences in the formation of equivalence classes. In Experiment 1, six typically developing children participated. They were ages 4-5 and were distributed in three conditions. All six children learned simple discrimination, but only one demonstrated the emergence of relations in the conditional discrimination probes. In Experiment 2, three other 5-year-old typically developing children participated. The three children learned simple discriminations and showed emergence of conditional relations in most of all probe blocks. In addition, in both studies, for children who tended to demonstrate the emergence of derived relations, differences were observed in the precurrent behaviors and prerequisites for both performing experimental tasks and establishing arbitrary relations. The results clearly indicate the occurrence of relational learning in young children, under certain conditions, and lead to new questions, both from the point of view of basic research and from the point of view of the development and evaluation of teaching conditions that can favor relational learning.
The learning of arbitrary relations in typically developing children
Keywords: Aprendizagem relacional; Comportamento simbólico; Consequências compostas específicas da classe; Relações arbitrárias; Discriminações condicionais; Classes de equivalência; Pré-escolares; Relational learning; Symbolic behavior; Fading; Compound class-specific reinforcers; Arbitrary relations; Conditional discriminations; Equivalence classes; Preschoolers; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL